1960
DOI: 10.1172/jci104065
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Significance of the Secretion of Endogenous Insulin Into the Portal Circulation. Iii. Evidence for a Direct Immediate Effect of Insulin on the Balance of Glucose Across the Liver*†

Abstract: There is at present general agreement, based upon abundant in vitro and in tvvo experimental evidence, that insulin exerts an immediate and profound effect on glucose utilization by muscle and adipose tissue (1-5). On the other hand, a direct hepatic action of insulin is disclaimed by most investigators since innumerable studies both in vitro and in vivo have failed to demonstrate clearly a consistent and reproducible effect of insulin upon hepatic glucose metabolism (5-12).Recent observations from this labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
2

Year Published

1969
1969
1987
1987

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(42 citation statements)
references
References 38 publications
3
37
2
Order By: Relevance
“…These data in the neonate are in marked contrast to that noted in the adults in our series and to that reported previously in the adult human and dog (17)(18)(19)(20). For example, Madison has suggested that the control of plasma glucose following insulin administration is a direct effect of insulin on liver rather than a peripheral insulin effect on muscle (17,18).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These data in the neonate are in marked contrast to that noted in the adults in our series and to that reported previously in the adult human and dog (17)(18)(19)(20). For example, Madison has suggested that the control of plasma glucose following insulin administration is a direct effect of insulin on liver rather than a peripheral insulin effect on muscle (17,18).…”
Section: Discussioncontrasting
confidence: 99%
“…In adults, numerous studies have clearly shown that both mechanisms are effectively operating to maintain normal plasma glucose concentration (10,(17)(18)(19)(20). In the newborn, the apparent inefficiency of glucose homeostasis incremental'glucose infusion was utilized in infants to infer the rate of basal glucose output compared to adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fasting animal glucose concentration is a function of glucose entry into plasma from the liver and its removal from the plasma by peripheral tissues [7]. This was demonstrated using hepatic vein catheterization by Madison et al [17] and more recently by Harding et al [18]. Steele [9,12] described a tracer infusion method which allowed measurement of the glucose fluxes through these two pathways and also enabled these measurements to be made in the non-steady state without the need to insert catheters across the liver and other tissues.…”
Section: Discussionmentioning
confidence: 97%
“…One method for calculating the rate of production of glucose involves measuring the rate of glucose influx into the liver (portal vein and hepatic artery), and subtracting from this the rate of effiux from the liver [3][4][5].…”
mentioning
confidence: 99%